2021
DOI: 10.56369/tsaes.3782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mexican Native and Hybrid Maize (Zea Mays) Silages for Sustainable Milk Production

Abstract: <p><strong>Background</strong>. Maize cultivation and dairy cattle represent two of the main economic activities in Mexico. <strong>Objective</strong>. Determine the forage yield (ton / ha) and forage quality of the maize silage produced in Mexico and estimate potential milk production. <strong>Methodology</strong>. For this purpose, 13 studies carried out in Mexico, were analyzed according to study area (north vs. center of Mexico) and variety (native vs. hybrid). For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
4
1
Order By: Relevance
“…Maize genotypes DK-390, San Pableño, VS-536, Impacto, and Chimbo were statistically similar and superior to Elotillo (Figure 2a). In the study conducted by Robles-Jimenez et al (2021), to determine the forage yield of maize landraces in Mexico authors reported an average of 279.1 g plant -1 which is higher than the dry matter observed in our study. These differences may be attributed to differences in maize genotypes and soil fertility.…”
Section: Dry Matter Allocation Grain Yield and Harvest Indexcontrasting
confidence: 78%
“…Maize genotypes DK-390, San Pableño, VS-536, Impacto, and Chimbo were statistically similar and superior to Elotillo (Figure 2a). In the study conducted by Robles-Jimenez et al (2021), to determine the forage yield of maize landraces in Mexico authors reported an average of 279.1 g plant -1 which is higher than the dry matter observed in our study. These differences may be attributed to differences in maize genotypes and soil fertility.…”
Section: Dry Matter Allocation Grain Yield and Harvest Indexcontrasting
confidence: 78%
“…These breeds are constituted of varieties known as local or criollas, and although they lack formal genetic improvement, they have adapted to the instability of the agroecological conditions of their environment through evolutionary processes [3,4], which is why they have even been used to generate improved varieties. The above evidence shows that native varieties play an important role for the resilience of the agricultural sector facing climate change, and that they constitute a valuable plant genetic resource not only for grain production, but also for forage production [5]. In this sense, it has been shown that there are native varieties of maize with potential for forage production, and that they can respond better than improved varieties in terms of dry-matter yield and nutritional value [6].…”
Section: Introductionmentioning
confidence: 97%
“…When considering these criteria, it has been estimated that contents of 88,270,229,431,225 and 49 g kg -1 of crude protein, starch, soluble carbohydrates, neutral detergent fiber, acid detergent fiber and ash, respectively, are obtained (Liu et al, 2021). Furthermore, net lactation energy values range from 1.09 to 1.55 Mcal kg -1 of dry matter (Robles-Jimenez et al, 2021). Improved seeds are currently used for maize forage production, with which grain and forage yields have increased.…”
Section: Introductionmentioning
confidence: 99%
“…However, these available genotypes may not thrive in the future as a result of climate change, since a combination of biotic (higher temperature, water deficiency) and abiotic (pest and pathogen attack) factors would significantly reduce production (Malhi et al, 2021). Native maize is a source of germplasm from which genotypes with improved tolerance mechanisms against environmental stressors could be obtained (Robles-Jimenez et al, 2021). Those native genotypes are indeed adapted to the specific environmental conditions prevailing where they are grown and of course with a lower investment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation